This much is certain. - Anderson, Kitty; Anderson, Kitty; Bonnell, Peter; Canépa Luna, Mariana; Gorton, Savannah; Hemelryk, Catherine; Lange, Christy; Lees, Nicola; Lorz, Julienne; Ormerod, Lucy; Svenle, Elna; Syson, Jennifer; et al. (London : Royal College of Art London, 2004)
Bäckström, Miriam ; Baker, Daniel ; Byrne, Gerard ; Dalwood, Dexter ; Deller, Jeremy ; Forsyth, Iain ; Pollard, Jane ; Yongping, Huang ; Jacir, Emily ; Massey, John ; Arnout, Mik ; Museum of Jurassic Technology ; Pieroth, Kirsten ; Shovlin, Jamie ; Vallance, Jeffrey
Exhibition, film, programme and talks curated by graduating students on the MA Curating Contemporary Art at the Royal College of Art.
This much is certain, Royal College of Art, London, 13 march - 4 april 2004
Engels
kunstcatalogus